2014
DOI: 10.1080/09168451.2014.942254
|View full text |Cite
|
Sign up to set email alerts
|

Cellular redox regulation, signaling, and stress response in plants

Abstract: Cellular and organellar redox states, which are characterized by the balance between oxidant and antioxidant pool sizes, play signaling roles in the regulation of gene expression and protein function in a wide variety of plant physiological processes including stress acclimation. Reactive oxygen species (ROS) and ascorbic acid (AsA) are the most abundant oxidants and antioxidants, respectively, in plant cells; therefore, the metabolism of these redox compounds must be strictly and spatiotemporally controlled. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 170 publications
(246 reference statements)
0
50
0
Order By: Relevance
“…The effect of NaCl in reducing APX activity has been described in other plant species, including in vitro grapevine plantlets (Ikbal et al, 2014), anger plants (Hernández et al, 2003) or in pea leaves (Hernández et al, 2001). Thus, APX activity seems to be crucial for plant stress tolerance as well as for growth and development (Shigeoka and Maruta, 2014). In a wheat mutant line, showing a 40% decrease in thylakoidal APX, a decline in P N as well as in growth and seed production was reported (Danna et al, 2003).…”
Section: Effects On the Antioxidative Metabolismmentioning
confidence: 95%
“…The effect of NaCl in reducing APX activity has been described in other plant species, including in vitro grapevine plantlets (Ikbal et al, 2014), anger plants (Hernández et al, 2003) or in pea leaves (Hernández et al, 2001). Thus, APX activity seems to be crucial for plant stress tolerance as well as for growth and development (Shigeoka and Maruta, 2014). In a wheat mutant line, showing a 40% decrease in thylakoidal APX, a decline in P N as well as in growth and seed production was reported (Danna et al, 2003).…”
Section: Effects On the Antioxidative Metabolismmentioning
confidence: 95%
“…Cytosolic APXs are considered the most important peroxidases to scavenging and maintaining H 2 O 2 homeostasis in cytosol (Davletova et al, 2005;Koussevitzky et al, 2008;Maruta et al, 2012;Pnueli et al, 2003;Suzuki et al, 2013b). These enzymes are present in large amounts, exhibit high activity, and the expression of their genes is strongly responsive to abiotic and biotic stresses (Shigeoka and Maruta, 2014). Moreover, experimental evidence obtained from Arabidopsis has suggested that these enzymes are crucial for cell signaling, antioxidant protection and photosynthesis (Davletova et al, 2005;Koussevitzky et al, 2008;Maruta et al, 2012;Pnueli et al, 2003;Suzuki et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…The cellular and organellar redox states play signaling roles in the regulation of gene and protein expression in a wide variety of plant physiological processes including stress acclimation (Shigeoka and Maruta 2014). Zhou and others (2012b) reported that hydrogen peroxide (H 2 O 2 ) generated by triphosphopyridine nucleotide NADPH oxidase in the apoplast of plant cells plays a crucial role in cold acclimation-induced tolerance.…”
Section: Introductionmentioning
confidence: 99%